2017
DOI: 10.1093/ejcts/ezx174
|View full text |Cite
|
Sign up to set email alerts
|

Ribcage kinematics during exercise justifies thoracoscopic versus postero-lateral thoracotomy lobectomy prompt recovery†

Abstract: clinicaltrials.gov (NCT02910453).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“… 8 Clinical studies on pulmonary function after lobectomy evidenced a reduction in volume variation on the side of surgery. 45 , 46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Clinical studies on pulmonary function after lobectomy evidenced a reduction in volume variation on the side of surgery. 45 , 46 …”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies reported a decrease in spirometry parameters (FVC and FEV1) after lobectomy, indicating an overall reduction of pulmonary function. 5 , 7 , 46 , 52 However, poor literature exists about local alteration of pulmonary function and fluid dynamics consequences. A recent clinical study on postoperative patients demonstrated the difficulty in measuring lobar ventilation redistribution through functional imaging (especially for surgery on the left side), due to the mediastinum shifting and geometry readaptation.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary endpoint of our study is the evaluation of early postoperative respiratory function, measured by pulmonary function tests. There is no doubt that the greatest impact on respiratory function is attributable to the parenchymal sacrifice following the pulmonary lobectomy itself; nevertheless, the type of surgical insult of the chest wall is significant as well [24]. Hence, multiple chest wall incisions can potentially impact the decreased respiratory function more than a single incision.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary endpoint of our study is the evaluation of early postoperative respiratory function, measured by pulmonary function tests. There is no doubt that the greatest impact on respiratory function is attributable to the parenchymal sacri ce following the pulmonary lobectomy itself; nevertheless, the type of surgical insult of the chest wall is signi cant as well [25]. Hence, multiple chest wall incisions can potentially impact the decreased respiratory function more than a single incision.…”
Section: Discussionmentioning
confidence: 99%